Pengaruh Rasio Efektivitas Pendapatan Asli Daerah, Rasio Efisiensi, Rasio Desentralisasi Fiskal, dan Rasio Kemandirian Daerah Terhadap Belanja Modal Provinsi Jawa Barat Tahun 2018-2022 - Thoha, Muhammad Nuur Farid; Novianti, Firsty Annisa (Prisani Cendekia, 2024)
This research was conducted to analyze the influence of the ratio of effectiveness of regional original income, efficiency ratio, fiscal decentralization ratio, and regional independence ratio on capital expenditure. The samples used in this research are 27 cities/regencies in West Java province 2018-2022. The sampling technique used a purposive sampling method and obtained 135 data samples from 27 cities/regencies. The data analysis technique used is panel data regression using Eviews 13 software. The results of this study indicate that the ratio of effectiveness of regional original income does not affect capital expenditure, the efficiency ratio of regional original income does not affect capital expenditure, the ratio of fiscal decentralization has a negative effect on capital expenditure, and The regional independence ratio has a positive effect on capital expenditure